Monolingual England: The Crisis in Foreign Language Enrollments from Elementary Schools through College - Godsland, Shelley (Hispania, 2010)
In 2005 the BBC reported that in reply to a survey conducted by the European Commission, 66% of English respondents indicated that they spoke no language other than their mother tongue. This proportion was far higher than in any other European Union nation taking part but compares fairly favorably with the United States, where one-fourth of adults are reported as being able to "speak a language other than English well enough to hold a conversation". In at least two areas key to the nation's knowledge economy, as well as its financial systems and markets, England's ability to compete and engage successfully is jeopardized when compared with other nations within Europe and beyond as a result of its citizen's poor or nonexistent language skills. This linguistic inability also compromises cross-cultural communication and comprehension. In 21st-century England, the languages deficit and strategies to overcome it are the subject of inquiry by governmental and other national deficit and strategies to overcome it are the subject of inquiry by governmental and other national bodies, and a range of policies has been developed to try to remedy its linguistic incompetence. A key impediment to achieving this, however, would appear to be the ongoing closure of languages departments and modern foreign language courses at English (and other British) universities. In this article, the author suggests some solutions to address England's foreign languages woes. (Contains 8 notes.)